Contemporary Women Poets - Michael Bishop (Studies in 20th & 21st Century Literature, 1989)
The essay evokes the essence of the respective démarches of eight major contemporary women poets: Janine Mitaud, Andrée Chedid, Marie-Claire Bancquart, Jeanne Hyvrard, Anne Teyssiéras, Martine Broda, Denise Le Dantec, Heather Dohollau. No attempt is made to generalise the findings of the individual analyses of collections and sample poems, though the following 'tensions' emerge as characteristically significant: the telluric and the cosmic; entropy and reintegration; body, mind and soul; passingness and search; language as problem and resolution; minimality and maximality; violence and love. In each poet high intensity is matched with wisdom and serenity, problematic though they may be. The poetic project of these women may be "fragmented" or more "coherent"; always it is marked by a profundity of perception and sentiment.
Keywords: démarches; respective; women poets; contemporary; anine Mitaud; Andrée Chedid; Marie-Claire Bancquart; Jeanne Hyvrard; Anne Teyssiéras; Martine Broda; Denise Le Dantec; Heather Dohollau; collections; tensions; telluric; cosmic; entropy; reintegration; body; mind; soul; passingness; search; language as problem; language; resolution; minimality; maximality; violence; love; high intensity; wisdom; serenity; poetic project; fragmented; coherent; profundity; perception; sentiment